INFLUENCE OF MICRO-COMPOSITION OF HIGH-MANGANESE AUSTENITIC STEEL ON MECHANICAL AND OPERATING CHARACTERISTICS OF CASTINGS - A. I. Garost (Литьë и металлургия, 2006)
It is shown at the example of wear-resistant of high-manganese steel that mechanical and operating characteristics depend to a great extent on micro-composition of deoxidation, connected with peculiarities of its production, deoxidation melting, modifying and micro-alloying. The carried out investigations prove the expediency of insertion of 1,30-1,38% chrome for improvement of its quality.